2010
DOI: 10.1017/s0025315410000974
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the harbour seal (Phoca vitulina vitulina) in the west and south-west of Ireland

Abstract: Although the harbour seal (Phoca vitulina vitulina) is relatively common in coastal waters of the Republic of Ireland, it remains largely unstudied. Issues including potential interactions with coastal fisheries and the occurrence of phocine distemper virus outbreaks in 1988 and 2002 have highlighted the need to increase our knowledge of the ecology of these animals. The diet of harbour seals was investigated using a combination of approaches: hard-part analysis of scat contents and fatty-acid analysis. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Unfortunately, research conducted on grey seal diet in Ireland is limited to a few studies in the 1990s . Furthermore, while both the Irish salmon aquaculture industry as well as rod and line fisheries in certain rivers/estuaries report substantial seal-related losses, particularly on the west coast , no evidence of salmonid remains have been identified in the diet of grey seals prior to this study, although salmonids have been recorded in the diet of harbour seals (Kavanagh et al 2010).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Unfortunately, research conducted on grey seal diet in Ireland is limited to a few studies in the 1990s . Furthermore, while both the Irish salmon aquaculture industry as well as rod and line fisheries in certain rivers/estuaries report substantial seal-related losses, particularly on the west coast , no evidence of salmonid remains have been identified in the diet of grey seals prior to this study, although salmonids have been recorded in the diet of harbour seals (Kavanagh et al 2010).…”
Section: Introductionmentioning
confidence: 79%
“…For example, studies in the northeast of Scotland have found very little evidence of salmonids in the diet (McConnell et al 1984, Prime & Hammond 1985. Kavanagh et al (2010) reported salmonids occurring in 3% of scat samples collected from harbour seal Phoca vitulina vitulina haul-out sites on the west coast of Ireland, but until now, no studies have found evidence of salmonids in the diet of grey seals in Ireland. Using bony material in addition to otoliths, this study has demonstrated that grey seals in southwest Ireland are consuming salmonids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated length and species preferences separately for grey seals (ΦLG and ΦsG) and harbour seals (ΦLH and ΦsH) using seal species‐specific diet data (Kavanagh et al . ; Gosch et al . ) and catchability‐corrected Irish Groundfish Survey data for the prey field; see Appendix S2.…”
Section: Methodsmentioning
confidence: 99%
“…Research on harbour seal diet in Ireland has been limited to studies conducted in Co. Down, Northern Ireland in the late 1990s [31], in Galway Bay in western Ireland 2001-2004, and in Bantry Bay and the Kenmare River in southwest Ireland since 2006 [32]. The studies suggest that harbour seals are opportunistic feeders as a wide variety of prey species were found in the diet of seals on both the west and southwest coasts, including 16 teleost species and two species of cephalopod, and there was seasonal and geographical variation in the diet evident.…”
Section: Dietmentioning
confidence: 99%